2018
DOI: 10.7554/elife.38588
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition enhances spatially-specific calcium encoding of synaptic input patterns in a biologically constrained model

Abstract: Synaptic plasticity, which underlies learning and memory, depends on calcium elevation in neurons, but the precise relationship between calcium and spatiotemporal patterns of synaptic inputs is unclear. Here, we develop a biologically realistic computational model of striatal spiny projection neurons with sophisticated calcium dynamics, based on data from rodents of both sexes, to investigate how spatiotemporally clustered and distributed excitatory and inhibitory inputs affect spine calcium. We demonstrate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
2
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 92 publications
(169 reference statements)
1
22
0
Order By: Relevance
“…The proximal and distal dendrites of SPNs differ in their regenerative capacity: brief glutamate uncaging at distal dendrites, but not proximal dendrites, evokes dendritic regenerative events that depolarize somatic potential for hundreds of milliseconds-so termed dendritic plateau potential (Plotkin et al 2011). Modeling predicts that spine calcium transients and dendritic plateau potentials are most effectively attenuated by distal GABAergic inputs at the site of excitatory inputs, whose primary function is to enhance input-specificity of local calcium elevation (Dorman et al 2018;Du et al 2017). Supporting this theoretical model, Du et al showed that dendritic plateau potentials are effectively attenuated by optogenetic activation of GABAergic synapses or GABA uncaging at "on-branch" dendritic site within a defined temporal window, but not by perisomatic GABAergic inhibition (Du et al 2017).…”
Section: An Increasing Role For Gabaergic Interneuronsmentioning
confidence: 99%
“…The proximal and distal dendrites of SPNs differ in their regenerative capacity: brief glutamate uncaging at distal dendrites, but not proximal dendrites, evokes dendritic regenerative events that depolarize somatic potential for hundreds of milliseconds-so termed dendritic plateau potential (Plotkin et al 2011). Modeling predicts that spine calcium transients and dendritic plateau potentials are most effectively attenuated by distal GABAergic inputs at the site of excitatory inputs, whose primary function is to enhance input-specificity of local calcium elevation (Dorman et al 2018;Du et al 2017). Supporting this theoretical model, Du et al showed that dendritic plateau potentials are effectively attenuated by optogenetic activation of GABAergic synapses or GABA uncaging at "on-branch" dendritic site within a defined temporal window, but not by perisomatic GABAergic inhibition (Du et al 2017).…”
Section: An Increasing Role For Gabaergic Interneuronsmentioning
confidence: 99%
“…We recognize that a stochastic approach would likely give rise to insights in limit cases of few molecules or in noisy environments [37,38]. Finally, we note that a more complete Ca 2+ influx model would account for voltage-gated calcium channel dynamics as well [22,24,60,61]. This is a focus of technical development and ongoing effort in our group.…”
Section: Discussionmentioning
confidence: 94%
“…Our finding that plasticity at a single synapse is influenced by neighboring synaptic activity is consistent with many studies (both in vivo and in vitro) showing relationships between spatial synaptic input patterns and plasticity. For instance, in SPNs in vitro, spatially clustered synaptic inputs can produce supralinear depolarization (termed NMDA-spikes or plateau potentials) and synaptic calcium transients (Plotkin et al, 2011;Dorman et al, 2018;Prager et al, 2020;Du et al, 2017), and synaptic activation of 2-4 neighboring spines at depolarized potentials can produce nonlinear enhancement of spine calcium transients (Carter et al, 2007). Building on these findings, our work predicts that neighboring synaptic interactions can influence the direction and magnitude of corticostriatal synaptic plasticity in vivo, with high neighboring activity producing LTP and low neighbor- Observations suggest that functional synaptic clustering is a key component in plasticity and learning.…”
Section: Discussionmentioning
confidence: 99%
“…Prior work has shown that synaptic plasticity can be affected by spatiotemporally cooperative synaptic activity-that is, multiple synapses on the same dendritic branch active within a limited time window (Govindarajan et al, 2011 shown that spatiotemporal activity patterns have nonlinear, spatially specific effects on calcium transients in dendrites and spines (Dorman et al, 2018). Thus, it is likely that nearby synaptic activity can cooperatively influence plasticity in our calcium-based model.…”
Section: Plasticity Of a Single Synapse Is Affected By Neighboring Synaptic Activitymentioning
confidence: 97%
See 1 more Smart Citation